2017
DOI: 10.1007/s00540-017-2352-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of body mass index on the risk of high spinal block in parturients undergoing cesarean delivery: a retrospective cohort study

Abstract: At standard spinal doses of hyperbaric bupivacaine used in our practice (≥10.5 mg), there were greater odds of high block in those with BMI ≥50 kg/m.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…8 A recent retrospective study also found a higher level of spinal block with increased vasopressor requirements in obese parturients with BMI > 50 kg m −2 16 compared to those with lower BMI. 17 Therefore without more prospective controlled studies it is still debated whether the local anesthetic dose should be further reduced in obese women.…”
mentioning
confidence: 99%
“…8 A recent retrospective study also found a higher level of spinal block with increased vasopressor requirements in obese parturients with BMI > 50 kg m −2 16 compared to those with lower BMI. 17 Therefore without more prospective controlled studies it is still debated whether the local anesthetic dose should be further reduced in obese women.…”
mentioning
confidence: 99%
“…Regional anesthesia puncture times for epidural and combined spinal-epidural may be prolonged in the obese patient, and may even contribute to delays in decision to delivery times seen in obese women [31,52]. There is a higher chance of regional anesthesia failures needing conversion to general anesthesia, and a higher chance of high block during spinal anesthesia necessitating general anesthesia in super obese women (BMI ≥ 50 kg/m 2) ) [31,53]. Still, dose reductions for spinal anesthesia have not been proven beneficial in obese patients [54].…”
Section: Anesthetic Considerationsmentioning
confidence: 99%
“…3 We believe avoidance of general anesthesia is a primary goal in the obese population to avoid the potentially difficult airway. 4 The inability to extend the duration of the block with a single-shot spinal technique may be a concern in the morbidly obese where the positioning and surgical procedure can take an extended period of time. The mean body mass index in our study participants was approximately 41 kgÁm -2 with surgery duration \ 60 min.…”
Section: To the Editormentioning
confidence: 99%
“…6 The use of a combined spinalepidural anesthesia at the L3/4 or L4/5 interspace may be technically easier than single-shot spinal anesthesia in the morbidly obese, also offering the flexibility to extend the duration of the block if needed. 4 With a carefully chosen intrathecal dose, a combined spinal-epidural is our preferred technique in the morbidly obese parturient (body mass index [ 50 kgÁm -2 ). 4 Conflicts of interest None declared.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation